Long range stress fields and cavitation along a shear band in a metallic glass: The local origin of fracture. (1st October 2015) - Maaß, R.; Birckigt, P.; Borchers, C.; Samwer, K.; Volkert, C.A.
Graphical abstract: Abstract: Nanomechanical properties along a single shear band in a Zr-based metallic glass were studied. Spatial mapping of both indentation hardness and modulus reveal complex long-range softening patterns that are indicative of internal stress fields along the shear band. These internal stresses reach values of the order of the yield strength of the tested metallic glass. Time dependent stress relaxation along the shear band is observed, and shear-band cavitation at the micron scale is found. Both the cavitation and the internal stresses are attributed to the non-planar shear plane that during shear-band propagation leads to the development of off-axis stress components relative to the shear direction. The cavities are a signature of a shear-band-to-crack transition, which is supported by stress fields known to develop ahead of mixed mode I and II crack tips.